Extraintestinal Infections Caused by Non-toxigenic Vibrio cholerae non-O1/non-O139 - Chowdhury, Goutam; Joshi, Sangeeta; Bhattacharya, Sanjay; Sekar, Uma; Birajdar, Balaji; Bhattacharyya, Arpita; Shinoda, Sumio; Ramamurthy, Thandavarayan (Frontiers in Microbiology, 2016)
Vibrio cholerae is an aerobic, sucrose fermentative Gram-negative bacterium that generally prevails in the environment. Pathogenic V. cholerae is well known as causative agent of acute diarrhea. Apart from enteric infections, V. cholerae may also cause other diseases. However, their role in causing extraintestinal infections is not fully known as it needs proper identification and evaluation. Four cases of extraintestinal infections due to V. cholerae non-O1/non-O139 have been investigated. The isolates were screened for their phenotypic and genetic characteristics with reference to major virulence genes. Serologically distinct isolates harbored rtx, msh and hly but lacked enteric toxin encoding genes that are generally existing in toxigenic V. cholerae. Timely detection of this organism can prevent fatalities in hospital settings. The underlying virulence potential of V. cholerae needs appropriate testing and intervention.